Voltammetric characterisation of silicon-based microelectrode arrays and their application to mercury-free stripping voltammetry of copper ions - Berduque, A.; Lanyon, Y.; Beni, V.; Herzog, G.; Watson, Y.; Rodgers, K.; Stam, F.; Alderman, J.; Arrigan, Damien (Elsevier, 2007)
Electrochemical sensors are of increasing importance in analytical chemistry due to their sensitivity, selectivity, fast and accurate analyses, portability and inexpensive cost [1]. The applications for such sensors vary widely from environmental and medical diagnostics to biotechnology and food and beverage analysis [2]. Improvements in electrochemical sensors include the development of modified electrodes (using chemical or biological recognition layers to improve the sensitivity and selectivity) and microelectrodes [3–5]. A microelectrode can be defined as an electrode in which at least one of its dimensions is in the m range [3] or an electrode with at least one dimension smaller than the diffusion length of the analyte [6].